Determinants of Student Satisfaction in Higher Education: Evidence from Indonesian Islamic Universities - Ahmad Fauzan; Sri Ilham Nasution; Misdarwati Misdarwati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Student satisfaction is an important benchmark for evaluating the quality of higher education services. This study aims to analyze the influence of teaching quality, educational facilities, social interaction, and faculty leadership on student satisfaction. The method used is a quantitative, survey-based approach. Data were collected through a structured questionnaire distributed to university students and analyzed using SmartPLS 4 to explore the direct and indirect relationships among variables. The study's findings indicate that teaching quality and faculty leadership have a significant, positive influence on student satisfaction. Although educational facilities are theoretically relevant, they pose ongoing challenges in practice. Social interaction contributes significantly to students' emotional and psychological well-being. Furthermore, faculty leadership mediates the relationship between input variables and student satisfaction, confirming the strategic role of leadership in improving the quality of educational services. The implications of this study emphasize the importance of strengthening visionary and participatory faculty leadership, improving the quality of student-oriented teaching, and managing an inclusive academic social environment as key strategies for sustainably improving student satisfaction and the quality of higher education. This study contributes to the theoretical refinement of student satisfaction as a multidimensional construct in Indonesian higher education.